Human Breast Milk: Exploring the Linking Ring Among Emerging Components - Bardanzellu, Flaminia; Fanos, Vassilios; Strigini, Francesca A. L.; Artini, Paolo G.; Peroni, Diego G. (Frontiers in Pediatrics, 2018)
ABSTRACT Maternal breast milk (BM) is a complex and unique fluid that evolution adapted to satisfy neonatal needs; in addition to classical nutrients, it contains several bioactive components. BM characteristically shows inter-individual variability, modifying its composition during different phases of lactation. BM composition, determining important consequences on neonatal gut colonization, influences both short and long-term development. Maternal milk can also shape neonatal microbiota, through its glycobiome rich in Lactobacilli spp. and Bifidobacteria spp. Therefore, neonatal nourishment during the first months of life seems the most important determinant of individual's outcomes. Our manuscript aims to provide new evidence in the characterization of BM metabolome and microbiome, and its comparison to formula milk, allowing the evaluation of each nutrient’s influence on neonatal metabolism.This result very interesting since potentially offers an innovative approach to investigate the complex relationship between BM components and infant’s health, also providing the chance to intervene in a sartorial way on diet composition, according to the nutritional requests. Future research, integrating metabolomics, microbiomics and stem cells knowledge, could make significant steps forward in understanding BM extraordinary properties and functions.